Re-evaluation of audit reports using Merton model The case of the traditional Syrian private banks listed on the Damascus Stock Exchange) - عمر الحارس, عبد الرحمن (Latakia University Journal - Economic and Legal Sciences Series, 2023)
Among the operating banks in Syria, there are many banks that have a Lebanese strategic partner, and these banks maintain investments of significant amounts in Lebanon. Because of the current conditions that the Lebanese economy and the banking sector are going through, there are great doubts about the extent of these banks’ ability to recover these amounts, and about their ability to continue if they are asked to form a full provision regarding to these investments in accordance with the requirements of International Accounting Standard No. 9. Proceeding from this point, this research aims to reassess the opinion of the Syrian auditor which is included in the audit report of the traditional Syrian private banks listed in Damascus Stock Exchange. This is in order to verify the extent to which the auditor takes into his consideration the future events that may affect the continuity of the company and the possibility of its failure. The Merton model was used as one of the structural models to predict the probability of default and the amount of loss given default for all studied banks at the level of provisions formed on 12/31/2022 and then at a level of provision covering the full value of investments in Lebanon according to the requirements of International Accounting Standard No. 9. then Comparing the results of the test in the two cases to determine the effect of forming a provision for the full value of investments in Lebanon to the probability of default and the loss given default for each of the studied banks. And then compare the results of the type of audit report issued for the studied banks in order to determine whether there is agreement to issue a qualified report against the banks that show higher risk levels than the current levels. The results of the Merton model test showed that at the level of provisions formed on 12/31/2022, there are no differences between all the studied banks, whether in terms of the probability of default or loss given default. However, the results of the test at the level of provisions of 100% of the investments in Lebanon, showed that the various banks were affected in varying proportions. The most affected banks were Byblos Bank - Syria in the first place, and the National Credit Bank in the second degree. As for the rest of the banks, the degree of impact is limited, according to the data of 12/31/2022. In comparison with the audit report, the results showed that there is complete agreement with the opinion of the auditor, who issued a qualified report to all the banks that did not form sufficient allocations for their investments in Lebanon.